2019
DOI: 10.1016/j.physa.2018.12.037
|View full text |Cite
|
Sign up to set email alerts
|

The high frequency multifractal properties of Bitcoin

Abstract: Following the new advances in encryption and network computing, Bitcoin emerged as a private sector system facilitating peer-to-peer exchange via distributed ledgers based on blockchains, driving a transformational change towards a global economy outside the core financial system. The main purpose of this paper is to examine the multifractal properties of the Bitcoin price using high frequency data. The methods used are the wavelet transform modulus maxima and the multifractal detrended fluctuation analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…In order to find the optimal GARCH model for the hybrid model, we provide AIC and BIC values in Table 2 and three measures to compare the performances of the models for forecasting volatilities in Table 3. According to the results in Table 2 and AIC and BIC criteria, EGARCH (3,3) model is the best model. On the other hand, according to the results in Table 3, we can see that the GJR-GARCH(1,1) model performs the best among the introduced GARCH family models.…”
Section: Hybrid Models and Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In order to find the optimal GARCH model for the hybrid model, we provide AIC and BIC values in Table 2 and three measures to compare the performances of the models for forecasting volatilities in Table 3. According to the results in Table 2 and AIC and BIC criteria, EGARCH (3,3) model is the best model. On the other hand, according to the results in Table 3, we can see that the GJR-GARCH(1,1) model performs the best among the introduced GARCH family models.…”
Section: Hybrid Models and Resultsmentioning
confidence: 97%
“…We first forecast the volatility of Bitcoin price using the classic GARCH family models. Concretely, we use GARCH, EGARCH and GJR-GARCH model among the GARCH family models and the (p, q) parameters ranging from (1,1) to (3,3). In order to find the optimal GARCH model for the hybrid model, we provide AIC and BIC values in Table 2 and three measures to compare the performances of the models for forecasting volatilities in Table 3.…”
Section: Hybrid Models and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of Bitcoin prices using high frequency data, in [38] it is shown that it exists a large degree of multi-fractality in all examined time intervals which can be attributed to the high kurtosis and the fat distributional tails of the series returns; in [39] there is evidence about the leverage effect as the most powerful effect in volatility forecasting; volatility is also analysed in [40] in terms of the property of the long memory parameter to be significant and quite stable for both unconditional and conditional volatilities at different time scales. Extending the study to several high frequency cryptocurrencies data, in [41] the investigation on stylized facts is developed in terms of the Hurst exponent of dependence between four different cryptocurrencies.…”
Section: Introductionmentioning
confidence: 99%